N-(4-Methylphenyl)-3-nitropyridin-2-amine - Akhmad, M.A.A.; Abdullah, Z.; Fairuz, Z.A.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Two independent molecules comprise the asymmetric unit of the title compound, C(12)H(11)N(3)O(2). These differ in terms of the relative orientations of the benzene rings as seen in the respective dihedral angles formed between the pyridine and benzene rings [17.42 (16) and 34.64 (16)degrees]. Both molecules are twisted about the amine-tolyl N-C bonds [respective torsion angles = 22.3 (5) and 35.9 (5)degrees] but only about the amine-pyridine N-C bond in the first independent molecule [respective torsion angles = -11.7 (5) and 0.8 (5)degrees]. Intramolecular N-H center dot center dot center dot O hydrogen bonds preclude the amine H atoms from forming significant intermolecular interactions. The crystal packing features intermolecular C-H center dot center dot center dot O and C-H center dot center dot center dot pi and pi-pi [centroid-centroid distance: pyridine-benzene = 3.6442 (19) angstrom and pyridine-pyridine = 3.722 (2) angstrom] contacts.